Meio ambiente do trabalho: relações interpessoais, impactos e proposta de recuperação - (:unkn) unknown (Universidade Brasil, 2024)
Bearing in mind that most people still have a restricted and simplistic concept of the environment, they often forget that it is characterized beyond natural aspects (flora, fauna, soil, air, water, etc.), encompassing, also, environments called artificial or constructed, of which the work environment stands out, the central object of this dissertation. The work environment constitutes an environment in which activities and work relationships occur, which can occur in closed or open spaces. This is a text prepared through qualitative research, developed through a bibliographical review, whose general objective is to conceptualize the work environment and examine how some factors, such as: communication noise, toxic leadership, moral harassment , sexual harassment, unequal treatment of workers, seen mainly from the perspective of discrimination, and environmental problems considered traditional, strongly influence the sustainability of the work environment, acting as if they were true environmental impacts. In the end, we seek to present some suggestions to recover the sustainability, especially social, of this environment, such as, for example, the need to remodel the organizational culture of work environments, empowering leaders for democratic, collaborative action and not directed solely for profit, as well as having clearer, more precise and respectful communication towards others.
Keywords: Impactos ambientais; Sustentabilidade; Restauração; Legislação Ambiental